Inclusive Access to Anti-Hoax Websites: A Comprehensive Examination of User Experiences among Persons with Disabilities in Indonesia - Rahmatul Furqan; Shabrina Syntha Dewi (Jurusan Teknik Informatika dan Komputer, 2025)
In an era of digital misinformation, the role of anti-hoax websites in disseminating accurate information is crucial. However, ensuring that these platforms are accessible to all users, including those with disabilities, remains a challenge. This research delves into the accessibility landscape of Indonesian anti-hoax websites, focusing on inclusivity for persons with disabilities (PwD) in accordance with WCAG 2.1 guidelines. The two selected websites for evaluation are prominent in the Indonesian context: